Consequences of prosocial and antisocial behavior for the recipient. (September 2016) - Al-Yaaribi, Ali; Kavussanu, Maria; Ring, Christopher
Abstract: Statement of problem: Although studies have examined antecedents of prosocial and antisocial behaviors in sport, little is known about the potential consequences of these behaviors for the recipient. In this research, we examined: (a) whether teammate prosocial and antisocial behaviors are related to athletes' effort, performance, enjoyment and anger during a match and the mediating role of enjoyment and anger (Studies 1 and 2); and (b) whether prosocial and antisocial behaviors are related to commitment to play for one's team and whether enjoyment and performance mediate these relationships (Study 2). Method: Right after a game, football/soccer ( N  = 203; Study 1) and basketball ( N  = 281; Study 2) players completed a multi-section questionnaire measuring the aforementioned variables. Results: Prosocial teammate behavior was positively related to effort, performance, and enjoyment, and enjoyment mediated the relationship between prosocial teammate behavior and effort and performance; prosocial teammate behavior was also positively related to commitment directly and indirectly through enjoyment and performance. Antisocial teammate behavior was positively related to anger and negatively related to effort and performance. Anger and performance mediated the effects of antisocial teammate behavior on effort and commitment, respectively. Conclusions: Our findings demonstrate the importance of acting prosocially and not acting antisocially toward one's teammates and have implications for enjoyment, effort, performance, and commitment in sport. Highlights: Prosocial teammate behavior positively affects enjoyment, effort, performance, and commitment during a competitive match. Antisocial teammate behavior negatively affects effort and performance and negatively affects anger. Enjoyment and anger mediated the effects of prosocial and antisocial teammate behaviors on effort and performance. Enjoyment and performance mediated the effects of prosocial and antisocial teammate behaviors on commitment.